Parenthood and the risk of diabetes in men and women: a 7-year prospective study of 0.5 million individuals - Peters, S; Yang, L; Woodward, M; Guo, Y; Chen, Y; Bian, Z; Millwood, I; Bragg, F; Zhou, X; Ge, P; Chen, B; Gao, Y; et al. (Springer Berlin Heidelberg, 2016)
Background: In women, higher parity has been associated with increased risk of diabetes later in life. It is unclear, however, whether this association is mainly due to biological effects of childbearing, or to socioeconomic and lifestyle factors associated with childrearing. We assessed the association between number of children and diabetes risk separately in women and men. Methods: In 2004-08, the nationwide China Kadoorie Biobank recruited 0.5 million individuals aged 30-79 (mean 51) from 10 diverse regions across China. During 7 years of follow-up, 8,840 incident cases of diabetes were recorded among 463,347 participants without prior cardiovascular diseases or diabetes. Multivariable Cox regression yielded sex-specific hazard ratios (HRs) and 95% confidence intervals (CI) for incident diabetes by number of children. Results: Overall, ~98% of all participants had children. In women, there was a J-shaped association between number of children and risk of diabetes. Compared to women with one child, the adjusted HRs for diabetes were 1.39 (95% CI 1.11, 1.73) for childless women, and 1.12 (1.07, 1.18) for two, 1.23 (1.16, 1.31) for three, and 1.32 (1.21, 1.44) for ≥four children. In men, there was a similar association with risk of diabetes, with the corresponding HRs being 1.28 (1.02, 1.60), 1.19 (1.12, 1.26), 1.32 (1.21, 1.44), and 1.41 (1.24, 1.60), respectively. In both sexes, the findings were broadly similar in different population subgroups. Conclusion: The similarity between women and men in the association between number of children and risk of diabetes suggests that parenthood is most likely to affect diabetes risk through factors associated with childrearing rather than via biological effects of childbearing.